The Relationship Between Cybervictimization and Anxiety Among Nursing Students at STIKES Dharma Husada - Rudianty, Vena Annisa; Ambarwaty, Mia Dwi; Hastuti, Emma Aprilia; Siagian, Indah Mentari (Karya Kesehatan Siwalima, 2025)
Cybervictimization is a form of violence or harassment conducted online, which can negatively affect psychological well-being, including increasing the risk of anxiety. Cybervictimization is particularly prevalent among late adolescents and young adults, as these age groups frequently use social media as a primary means of daily interaction. This study aimed to examine the association between cybervictimization and anxiety levels among nursing students at STIKes Dharma Husada. A quantitative method with a correlational design and a cross-sectional approach was employed. The study sample consisted of 76 respondents. The research instruments included the Cybervictimization Scale (CYBVICS) and the Generalized Anxiety Disorder-7 (GAD-7). Data were analyzed using Spearman’s rank correlation test. The findings showed that half of the respondents experienced moderate levels of cybervictimization (50.0%), and most reported severe anxiety (56.6%). The correlation analysis revealed a significant association between cybervictimization and anxiety, with a p-value of 0.001 and a correlation coefficient of 0.449, indicating a moderate positive relationship. In conclusion, the higher the level of cybervictimization experienced, the higher the level of anxiety among students. Based on these findings, it is recommended that educational institutions and students increase efforts to prevent and manage the psychological impacts of digital violence.